Environmental mutagens and possibilities for prevention - Anwar, Wagida A. (European Journal of Oncology and Environmental Health, 2004)
Humans are exposed to many physical or chemical genotoxic agents that can increase the probability of mutation. On the other hand, there are possible ways to prevent this effect. One of them is to prevent cellular injury by augmenting endogenous oxidative defences through the dietary intake of antioxidants such as vitamin C or vitamin E. Also olive oil has proved to have potent antioxidant properties. Several studies have been conducted during the last ten years to demonstrate the genotoxic effect of these environmental pollutants, and to investigate possible protective effects. In one of these studies, we investigated the mutagenic effects of two commonly used pyrethroid pesticides, cypermethrin and fenvalerateon, on bone marrow cells of adult male rats and the possible protective rôle played by olive oil and vitamin C. Results revealed that cypermethrin and fenvalerate induced a significant increase in the total number of chromosomal aberrations, and that more were observed with fenvalerate. Olive oil and vitamin C induced significant improvement of total aberrant cells at high doses (1/10 LD50). Aflatoxins contaminate many food products and are consequently of worldwide heath concern. Prevention of exposure to aflatoxins can be achieved either at community (via good agriculture practices) or individual levels (treatment or dietary interventions). Several trials were carried out to evaluate the effect of the processing steps of corn products on the destruction of aflatoxins in popcorn. The results of the trial indicated that the processing of popcorn had a significant effect on aflatoxin destruction. High temperature of preparation and treatment with 5% salt (sodium chloride) yielded the highest destruction rate. Several probiotic bacteria are able to bind aflatoxin B1 (AFB1) in vitro, including Lactobacillus rhamnosus LC-705 and Propionibacterium freudenreichii subsp. shermanii JS. A mixture of these two probiotics is used by the food and feed industry as biopreservative (Bioprofit), making it a promising candidate for future applications. A recent study was carried out to determine whether administration of probiotic bacteria could block the intestinal absorption of aflatoxin B1. Probiotic administration led to a statistically significant decrease in the urinary excretion of AFB-N7-guanine. Probiotic supplement reduces the biologically effective dose of aflatoxin exposure, and may thereby offer an effective dietary approach to prevent the development of liver cancer. An other example of these studies is that on the radioprotective rôle of vitamin C and E against gamma radiation-induced depletion in relative testicular weight and sperm shape abnormalities.